Utilização de misturas de coprodutos em rações de vacas leiteiras - Ferreira, Lorrany Bento (2016)
The objective of this study was to evaluate the partial replacement of corn silage and concentrate mixtures of by-products on the dry matter intake, milk yield and composition, conditioned meal, apparent digestibility in the digestive tract and feeding behavior of dairy cows. Nine multiparous lactating cows, coming from Holstein x Jersey cross, were confined in tie stall stalls and used Latin square 3x3 replicated, with periods of 18 days. The treatments were (% DM): Control - 53.5% corn silage and 46.5% concentrate; Mixture 1-43% corn silage, 30% concentrate and 27% of by-products of mixture 1 and Mixture 2-18% corn silage, 31% concentrate and 51% of by-products mixture 2. The feed was provided individually twice a day in complete diet. In each period, the offered food, leftovers and feces were collected, quantified and analyzed for dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), neutral detergent fiber ( NDF) and mineral matter (MM) to determine the intake and digestibility. The production of milk was recorded at the end of each experimental period, wherein the milk samples were collected and composed of two daily milkings and analyzed for fat, protein and lactose. The conditioned meal was assessed on days one, seven, and 14 of the experimental period, in which the feed was weighed two hours after its supply in the morning. The masticatory activity was visually assessed every 5 minutes for 24 hours. Statistical analysis was performed with PROC MIXED SAS and the means compared by Tukey test at 5% significance level. The dry matter intake, production and composition of milk did not differ (P>0.05) between treatments Control and Mixture 1. Mixture 2 treatment decreased (P<0.05) dry matter intake (13.2 vs. 15.9 kg /d) producing corrected milk fat (22.7 vs. 25.3 kg / d), fat content (3.63 vs. 4.06%), protein (2.87 vs. 3.07 %) and lactose milk yield (1.11 vs. 1.17 kg / day) compared to the Control treatment. There was no effect (P>0.05) on the digestibility of DM, OM and NDF between Control and Mixture 1 treatments, however the Mixture 2 treatment DM digestibility (65.8 vs. 58.4%) and MO (68.6 vs. 60.6%) were higher (P<0.05) compared to Control. MS consumption in the conditioned meal was lower (P<0.05) on day seven and 14 for Mixture the 2 treatment compared to the Control. The intake variables, rumination and chewing did not differ (P> 0.05) between the Control and Mixture 1. Mixture 2 and the treatment rumination times (425 min/d) and chewing (640 min/d) were lower (P<0.05) compared to Control. The Mixture 1 treatment can be used without loss in animal productivity, however treatment Mixture 2 depressed the dry matter intake, milk production and solid content.